2015 15th International Conference on Control, Automation and Systems (ICCAS) 2015
DOI: 10.1109/iccas.2015.7364838
|View full text |Cite
|
Sign up to set email alerts
|

Humanoid robot based on the middleware CORBA

Abstract: Intelligent humanoid robot (lHR) consisting of intelligent software components is proposed in this paper. The framework of an IHR requires reliable and stable network connection with real-time response between software components. In the developed service platform, intelligent software components work on the resources that are distributed in the network, and the IHR uses the results from the resources. In this way, the IHR is able to provide high-quality and intelligent service to users. In this framework, mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…While [51] proposed a resource management framework using CORBA. The CORBA architecture was also used in the development of an Intelligent Humanoid Robot (IHR) [52]. The study is focused on the object-oriented design of the class scheduling model.…”
Section: Corbamentioning
confidence: 99%
“…While [51] proposed a resource management framework using CORBA. The CORBA architecture was also used in the development of an Intelligent Humanoid Robot (IHR) [52]. The study is focused on the object-oriented design of the class scheduling model.…”
Section: Corbamentioning
confidence: 99%
“…Many studies have been conducted and have reported on robot-based automation of the shoe manufacturing process [3][4][5][6][7][8][9][10][11][12][13][14]. Ding et al proposed a methodology for measuring foot girths using a local radial basis function [3].…”
Section: Introductionmentioning
confidence: 99%
“…Most research has focused on the specific process of automation or the development of a fundamental algorithm. In our previous study [14], we proposed the concept of a robot-based automation system for upper and sole manufacturing with preliminary results.…”
Section: Introductionmentioning
confidence: 99%